2011
DOI: 10.1007/s12013-011-9254-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Uremia on Semen Quality and Reproductive Function in Humans

Abstract: In this study, we sought to evaluate the effect of uremia on semen quality and reproductive function in humans. For this purpose, 53 end-stage uremic patients were randomly selected. The semen samples were produced by masturbation. Fertility index (FI) was calculated according to the following formula: sperm density (×10(6)/ml) × sperm motility (%) × normal sperm morphology rate (% per 10,000). The semen samples of uremic patients were compared with those of fertile and infertile males. The results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Kosar et al The explanation of the decrease in mean ST levels in unhealthy men in sub/infertility studies are not well known, but it is hypothesized that it is due to the action of interleukin-6 (IL6) in testis to reduces transferrin secretion in Sertoli cells (15). All sperm cell parameters evaluated (Table 1) were significantly lower in the case group than in the control group (p = 0.000), corroborating partially the results of other authors (16,17) that did not found significant differences for all the elements of the SP (16,17). However there is a study that did not show a significant difference in ST levels between healthy subjects and those with seminal quality alterations (18).…”
Section: Discussionsupporting
confidence: 76%
“…Kosar et al The explanation of the decrease in mean ST levels in unhealthy men in sub/infertility studies are not well known, but it is hypothesized that it is due to the action of interleukin-6 (IL6) in testis to reduces transferrin secretion in Sertoli cells (15). All sperm cell parameters evaluated (Table 1) were significantly lower in the case group than in the control group (p = 0.000), corroborating partially the results of other authors (16,17) that did not found significant differences for all the elements of the SP (16,17). However there is a study that did not show a significant difference in ST levels between healthy subjects and those with seminal quality alterations (18).…”
Section: Discussionsupporting
confidence: 76%
“…Xu et al (16) found similar results in a uremic population: 0.68 (2.08) for case and 7.7 (13.51) for control.…”
Section: Discussionmentioning
confidence: 55%
“…After the contribution of uremic factor in the lowering of seminal quality in patients with renal failure was recognized (16,20), the contribution of the oxidative/inflammatory factors was emphasized (21,22). Patients undergoing hemodialysis can be characterized by increased levels of oxidative stress and inflammation (23).…”
Section: Discussionmentioning
confidence: 99%
“…Changes to the function of the hypothalamic-pituitary-ovarian/testis axis in patients with chronic renal failure or severe hepatic dysfunction may result in anovulation or azoospermia. Uremia causes a significant decline in reproductive function and sperm quality which may lead to infertility or even sterility in humans (7). The earlier the onset, pre or post-pubertal, and the longer the duration of uremia, the more impairment the reproductive function in the human (8).…”
Section: Discussionmentioning
confidence: 99%